2011
DOI: 10.1002/qj.966
|View full text |Cite
|
Sign up to set email alerts
|

The Brewer–Dobson circulation inferred from ERA‐Interim

Abstract: 9 kg s −1 , with the zonal drag from resolved waves and parametrized orographic gravity wave drag (OGWD) providing 70% and 4% of the driving, respectively. Hence it is concluded that the OGWD probably underestimates the momentum deposited above 70 hPa in addition to there being an absence of drag from non-orographic gravity waves. A statistically significant trend of −5% per decade in the upwelling mass flux is considered unreliable because it is inconsistent with the negative temperature trend, assuming a mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
129
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(157 citation statements)
references
References 31 publications
26
129
2
Order By: Relevance
“…After 1995 the ERA-Interim data show a negative trend in the tropical upward mass flux (at 70/74 hPa), which is not captured by the model simulations. As shown by Seviour et al (2012), this negative trend contains large uncertainties, and does not occur in other reanalysis systems or when using different estimates of upwelling in ERA-Interim (Abalos et al, 2015). The nudged simulations, especially the simulations RC1SD-base-09/10 without global mean temperature nudging, are closer to ERA-Interim data than the RC1-simulations without nudging.…”
Section: Stratospheric Dynamicsmentioning
confidence: 73%
“…After 1995 the ERA-Interim data show a negative trend in the tropical upward mass flux (at 70/74 hPa), which is not captured by the model simulations. As shown by Seviour et al (2012), this negative trend contains large uncertainties, and does not occur in other reanalysis systems or when using different estimates of upwelling in ERA-Interim (Abalos et al, 2015). The nudged simulations, especially the simulations RC1SD-base-09/10 without global mean temperature nudging, are closer to ERA-Interim data than the RC1-simulations without nudging.…”
Section: Stratospheric Dynamicsmentioning
confidence: 73%
“…The mean residual vertical velocity in the transformed Eulerian mean framework, calculated using the same method as Seviour et al (2012), and the dynamical heating used in Sect. 4 are both computed on the original grid from the ERA-Interim data and then smoothed by lin-early interpolating the monthly averages to daily values.…”
Section: Data and Radiative Methodsmentioning
confidence: 99%
“…We first consider the variations in the upwelling from below by the residual vertical velocity, w*. A large annual cycle in tropical w*, averaged over the tropics, has been reported [Rosenlof, 1995;Randel et al, 2007Randel et al, , 2008Yang et al, 2008;Seviour et al, 2012], but there has been less examination of the latitudinal variations within the tropics. These previous studies have also shown differences among w* obtained from different meteorological reanalysis products, so we examine w* from three reanalyses: ERA-40 [Uppala et al, 2005], ERA-Interim [Seviour et al, 2012], and Modern-Era Retrospective Analysis for Research and Applications (MERRA) [Rienecker et al, 2011].…”
Section: Seasonal Variations In Transportmentioning
confidence: 99%